Social control in the National School Feeding Program: limits and potentialities of the work of the Councils in Paraná - Silva, Christian Luiz da; Muniz, Dalton Metz (Interações (Campo Grande), 2022)
The School Meals Council (CAE) is an instrument that aims to offer conditions for the population to have a direct assessment of how the National School Feeding Program (PNAE) is executed and to establish channels for charging the governments regarding improvements demanded. In the face of so many challenges to strengthen the PNAE and its social control, there is an interest in deepening the theme, contributing to a better understanding of the context of CAE's performance, to allow reflection for the design of initiatives that promote the principles of social participation in the context of school feeding. To this end, a social and applied research was developed, with three phases, exploratory, descriptive, and analytical, to verify the normative and organizational aspects, as well as how many CAEs in Paraná and the respective managements of a given sample met the minimum transparency requirements required by the PNAE legislation. Among the main results, it was found that the CAE has a relevant role for the management of the PNAE, but its challenges and limitations are evident when analyzing a few attributions, such as monitoring schools and providing information about their performance. While the relationship between counselor and school proved to be an action potential in small and medium-sized municipalities, in administrations with more than 70 school units, the challenges and bottlenecks increase considerably. Regarding the provision of information to the public, only 15% among 146 different administrations presented at least one institutional space for the CAE on their websites, and 6% only made minutes available for consultation, illustrating the low transparency regarding the performance of these CAEs.